An eyeball diagram: illustrating the common CSFs in e-commerce business satisfaction for successful adoption of e-commerce systems by SMEs. (1st January 2012) - Wu, Mingxuan; Jewell, Rod; Gide, Ergun
Previous research has determined that the measurement of business satisfaction (e-commerce business satisfaction – EBS) with e-commerce success could be a better determinant of successful business adoption of an e-commerce system than measuring from a customer perspective. The aim of this continuing research is to determine if common critical success factors (CSFs) exist for EBS across different countries. Based on 73 initial items from previous research, a blend of quantitative and qualitative research methods was used to gather data from SMEs in Australia and China. The data were analysed using repeated reliability analysis comprising initial reliability analysis, validity analysis, one-sample t-testing, identification of common items, independent-samples t-testing, factor analysis, and detailed reliability analysis. A total of 15 items were identified as Common CSFs . An eyeball diagram illustrates the Common CSFs and their relationships. Further research is needed using the Common CSFs as a basis to develop a more effective tool for SMEs to successfully adopt an e-commerce system.